Mechanism for the Appointment of Acting Regional Heads Who Participate in the Simultaneous Regional Elections - Adrian, Rifki; Nasution, Faisal Akbar; Sihombing, Eka N A M; Sutiarnoto, Sutiarnoto (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Regional Heads, which are often not in accordance with the Constitutional Court Decision Number 67/PUU-XIX/2021, that in choosing the Acting Head, it must be measurable and clear that it does not ignore the principles of democracy, pay attention to regional aspirations and be carried out openly, transparency and accountability. This is because there is no regulation that contains how the mechanism for electing Acting Regional Heads is permanent, so that it leads to centralistic conflicts of interest in local governments.Purposes of the Research: To examine in this study what the Mechanism for Appointment of Acting Regional Heads Who Participate in the Simultaneous Regional Elections.Methods of the Research: The research method carried out is normative legal research with a statutory research approach (Statue Approach). The data sources used were secondary data with Premier legal material, secondary legal material and Tresier Law material, data analysis used by Qualitative method. This research discusses the arrangement, appointment mechanism, as well as the duties and authorities of acting regional heads in the context of the implementation of the Simultaneous Regional Elections in Indonesia.Results Main Findings of the Research: The findings of the study show that the regulation of acting regional heads is regulated in Article 201 of Law Number 10 of 2016 and Regulation of the Minister of Home Affairs Number 4 of 2023. However, this arrangement is not in accordance with the principle of a just and democratic state of law. The mechanism for appointing acting regional heads also does not involve community participation and tends to be centralistic. Meanwhile, the duties and authority of the acting regional head refer to the definitive duties and authorities of the regional head, although there are certain limitations. Therefore, rules are needed that are more in line with the principles of the state of law and democracy, and involve community participation in the process of appointing acting regional heads. In addition, the government needs to consider regional aspirations in appointing acting regional heads.